Narrative design : - Bell, Madison Smartt (Norton & Company, 2000)
Unconscious mind -- Linear design. Depth charge / Craig Bernardini ; A wife of Nashville / Peter Taylor ; Daisy's Valentine / Mary Gaitskill ; Hear that long train moan / Percival Everett ; Oh, man alive / Holden Brooks ; The sky is gray / Ernest J. Gaines -- Modular design. Signs of life / Miriam Kuznets ; Lizzie, Annie, and Rosie's rescue of me with blue cake / Carolyn Chute ; The child downstairs / Marcia Golub ; Red hands / William T. Vollmann ; Comic strip / George Garrett ; Little Red / Gilmore Tamny -- A philosophy of composition.